Influence of contact medium and surfactants on carbon dioxide clathrate hydrate kinetics - Kumar, Asheesh; Sakpal, Tushar; Linga, Praveen; Kumar, Rajnish (Fuel, 2013)
Carbon dioxide (CO2) hydrate formation kinetic was investigated in a fixed bed crystallizer at constant pressure (3.55 MPa) and temperature (274 K). Porous media of three different silica gels were used, with a mesh size of 60-120, 100-200 and 230-400 having different surface area. The observed trends indicate that silica gel with larger surface area leads to higher gas consumption as well as reduces the induction time. The effect of pore diameter and particle size distribution has already been reported in a previous study [1]. In this study the effect of additives on hydrate formation kinetics were also investigated. The additives studied were nonionic surfactant Tween-80 (T-80), cationic dodecyltrimethylammonium chloride (DTACl) and anionic Sodium Dodecyl Sulphate (SDS). Out of the three surfactants used in this study, SDS was found to be most effective in enhancing the rate of hydrate formation as well as reducing the induction time. The current result shows significant improvement in water to hydrate conversion in silica gel media compared to quiescent water or surfactant-water system under similar conditions. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate hydrate; kinetics; Silica gel; Surfactants